2002
DOI: 10.1111/j.1572-0241.2002.07063.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different probiotic preparations on anti-Helicobacter pylori therapy-related side effects: a parallel group, triple blind, placebo-controlled study

Abstract: All the probiotics used were superior to placebo for side effect prevention, but were not associated with better compliance with antibiotic therapy. The effect of probiotic supplementation on side effects during anti-H. pylori regimens seemed to be independent of the probiotic species used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
161
1
6

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 290 publications
(173 citation statements)
references
References 18 publications
5
161
1
6
Order By: Relevance
“…Four of these studies found a statistically significant reduction in the incidence of AAD with LGG use in comparison to placebo [19,20,21,22]. One study found a significant decrease in the number of days of diarrhoea in the LGG group compared to placebo [18].…”
Section: Resultsmentioning
confidence: 99%
“…Four of these studies found a statistically significant reduction in the incidence of AAD with LGG use in comparison to placebo [19,20,21,22]. One study found a significant decrease in the number of days of diarrhoea in the LGG group compared to placebo [18].…”
Section: Resultsmentioning
confidence: 99%
“…Figure 2 shows the results of the methodological quality assessment. The allocation concealment was unclear in one RCT [17], and another trial [15] was at high risk of binding. The remaining two trials had good methodological quality.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Three RCTs were placebo controlled [16]- [18], and there was no additional intervention in the control group in the other one trial [15]. The included studies were conducted in Italy (three RCTs) [15]- [17] and Egypt (one RCT) [18]. Figure 2 shows the results of the methodological quality assessment.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations